Technical readiness indices study of a female runner at 100 and 200 meters in the Olympic season - Yamaletdinova, G. A.; Spirina, M. P.; Kizilov, L. I. (The Russian Journal of Physical Education and Sport, 2019)
The increased level of sports results in sprint, the increasing competence level in this kind of track and field activity make the problem of reliability and stability of female runners` performances in different competitions very urgent. One of the ways in this direction is technical mastery improvement on the basis of competitive and training influences control. Materials. The article presents the results of technical readiness indices of a female runner for 100 and 200 meters, shown during All-Russian competitions before the Olympic Games. These indices are received as a result of track and field complex scientific group (CSG) mutual work and the athlete`s coaches national team of Russia. Research methods. Comparative-contrastive, system analysis of psychological-pedagogical literature, sports experience study and summarizing, competitions protocols, technical mastery level study according to the time of running the distance, speed of running, the number of running steps, length of the running steps, frequency of the running steps, the percentage of parameters contribution from maximum value (100 meters running) according to different parts of 100 and 200 meters distance. Results. Sprint is characterized by maximum intensity of all distances overcoming in an anaerobic regimen. 100 meters running is divided into start and starting stride (0-30 meters), (30-60 and 60-80 meters) distance running and maximum possible speed preserving during the final part of the distance (80-100 meters).The results analysis and handling was realized according to the given parts of the distance. In 200 meters running the most significant indices are the following: time, speed of running, length, frequency and number of steps at different parts of the distance. We analyzed the following parts of the distance: 0-100, 100-150, 150-200 meters. The level of special endurance was defined according to the difference between running the first and the second parts of the distance. Conclusion. The results, received during the athlete`s competitive activity study at 100 and 200 meters running, helped to reveal technical readiness level during the current moment and model the program of trainings during training for the Olympic Games.